Statistical process control for the food industry: a guide for practitioners and managers - Lim, Sarina A.; Antony, Jiju (John Wiley & Sons, 2019)
This book provides managers, engineers, and practitioners with an overview of necessary and relevant tools of Statistical Process Control, a roadmap for their implementation, the importance of engagement and teamwork, SPC leadership, success factors of the readiness and implementation, and some of the key lessons learned from a number of food companies. Illustrated with numerous examples from global real-world case studies, this book demonstrates the power of various SPC tools in a comprehensive manner. The final part of the book highlights the critical challenges encountered while implementing SPC in the food industry globally. Statistical Process Control for the Food Industry: A Guide for Practitioners and Managers explores the opportunities to deliver customized SPC training programs for local food companies. It offers insightful chapter covering everything from the philosophy and fundamentals of quality control in the food industry all the way up to case studies of SPC application in the food industry on both the quality and safety aspect, making it an excellent "cookbook" for the managers in the food industry to assess and initiating the SPC application in their respective companies. Covers concise and clear guidelines for the application of SPC tools in any food companies' environment Provides appropriate guidelines showing the organizational readiness level before the food companies adopt SPC Explicitly comments on success factors, motivations, and challenges in the food industry Addresses quality and safety issues in the food industry Presents numerous, global, real-world case studies of SPC in the food industry Statistical Process Control for the Food Industry: A Guide for Practitioners and Managers can be used to train upper middle and senior managers in improving food quality and reducing food waste using SPC as one of the core techniques. It's also an excellent book for graduate students of food engineering, food quality management and/or food technology, and process management.